Prioritas Ibadah Di Masa Pandemi - esthi sa’adatus tsani (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
Abstract : Worship Priorities During The PandemicCongregational worship activities caused mass groups to become a problem during the Covid19 pandemic. This study aims to determine the priority of a Muslim's worship during a pandemic. The focus of this research problem is related to how the priority of a Muslim's worship in the face of a pandemic. This research method is a literature study and uses a descriptive qualitative approach. The results of the research prove that in conditions during the pandemic a Muslim continues to cultivate Islamic values through awareness to worship and improve the quality of worship because worship is an obligation and priority for a servant. Because during the pandemic, there were still Muslim community members who worshiped in the mosque, so the village issued a policy to maintain cleanliness, use masks and maintain a distance of one to two meters when praying in the mosque.